AN EDITORIAL ABOUT BROADER MEANING IN ARCHITECTURE - Harsritanto, Bangun Indrakusumo Radityo (architecture department, Engineering faculty, Universitas Diponegoro, 2024)
On this Vol 24 no1, MODUL has published 5 scienteific articles. With compiling the information of all published articles, this editorial try to provide scientific information about “the meaning”